2018
DOI: 10.1371/journal.pone.0201004
|View full text |Cite
|
Sign up to set email alerts
|

Prospective and longitudinal natural history study of patients with Type 2 and 3 spinal muscular atrophy: Baseline data NatHis-SMA study

Abstract: Spinal muscular atrophy (SMA) is a monogenic disorder caused by loss of function mutations in the survival motor neuron 1 gene, which results in a broad range of disease severity, from neonatal to adult onset. There is currently a concerted effort to define the natural history of the disease and develop outcome measures that accurately capture its complexity. As several therapeutic strategies are currently under investigation and both the FDA and EMA have recently approved the first medical treatment for SMA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
109
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 60 publications
5
109
1
1
Order By: Relevance
“…Nevertheless, a previous study reported an increased T2 in the upper leg in SMA patients, ranging from 34.3 to 41.3 ms, but this cannot be directly compared with our data as the authors used a multi-exponential signal model that does not account for EPG effects. 23 Moreover, Bonati et al found a strongly increased T2…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, a previous study reported an increased T2 in the upper leg in SMA patients, ranging from 34.3 to 41.3 ms, but this cannot be directly compared with our data as the authors used a multi-exponential signal model that does not account for EPG effects. 23 Moreover, Bonati et al found a strongly increased T2…”
Section: Discussionmentioning
confidence: 98%
“…21,22 Quantitative MRI in SMA has not been studied in detail. 16,23,24 The application of qMRI in diseased muscle proposes some technical challenges, as T2 signal and DTI parameters can be influenced or are confounded by fat present in the muscle. 21,25,26 This study aims to document qMRI properties of muscle tissue in SMA.…”
Section: Introductionmentioning
confidence: 99%
“…Several relatively small studies previously evaluated the natural history of lung function in patients with SMA [10][11][12][13][14][30][31][32][33][34][35][36][37][38]. FVC was studied most frequently and progressive FVC decline has been reported, caused by progressive respiratory muscle failure, limited lung and chest wall growth, and scoliosis progression [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…It is the most important cause of morbidity and mortality in patients with SMA [2,6]. Previous longitudinal studies of lung function included relatively small numbers of SMA patients, did not encompass the entire spectrum of severity or ages, focused on Forced Vital Capacity only, or had limited follow-up [10][11][12][13][14][15]. Additional natural history data of SMA patients treated according to the standards of care [6], but prior to receiving recently introduced therapies, are important to further improve timing of supportive care and to explore its potential as an outcome measure to evaluate longer-term effects of new treatment strategies [2,9,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Hereditary proximal Spinal Muscular Atrophy (SMA) is a severe neuromuscular disorder with predominantly infantile or childhood onset and is caused by deficiency of the survival motor neuron (SMN) protein due to loss of function of the SMN1 gene [1]. SMA is characterised by progressive loss of muscle strength and motor function with a large clinical variety ranging from severe hypotonia in the first months of life (type 1), stalled gross motor development but the ability to sit without support (type 2), difficulties with or the loss of ambulation later in life (type 3) to relatively mild impairments in adulthood (type 4) [2][3][4][5]. Fatigability, defined as the inability to sustain repetitive physical activities, is increasingly being recognized as an important additional dimension of physical impairments and a target for therapeutic interventions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%